The role of TNP-Nucleotides, LYS492 and CA²⁺chelators in the skeletal muscle sarcoplasmic reticulum CA²⁺atpase cycle - Wichmann, Janine (Division of Chemical Pathology, 2018)
In the first part of this study, the kinetics of decay of TNP-nucleotide superfluorescence was investigated with a view to understanding the role of nucleotides and Lys492 in later steps in the catalytic cycle of the skeletal muscle Ca²⁺ATPase. It has been found previously, and verified here, that tethering TNP-8N₃-AMP to the Ca²⁺ATPase via Lys492 retarded the Ca²⁺ initiated decay of Pᵢ-induced superfluorescence 10-fold compared with untethered nucleotide. The rapidity of the decay upon addition of EDTA suggested that the E₂ ↔ E₁ → E₁Ca₂ steps were being monitored rather than dephosphorylation per se. Tethered diand triphospho species did not accelerate the decay. While monophasic kinetics was observed with untethered TNP-AMP and TNP-8N₃-AMP, complex kinetics were observed with the di- and triphospho TNP-nucleotides. This was shown to be due to the utilization of TNP-ADP and -ATP, and the azido derivatives, as coupled substrates of the Ca²⁺ATPase in the forward direction of catalysis in the presence of Ca²⁺. The hydrolysis rates of TNP-ADP, TNP-ATP, TNP-8N₃ -ADP, and TNP-8N₃ -ATP were 10, 5, 15 and 10 nomoles/min/mg of protein, respectively, at room temperature and pH 5.5. Ca²⁺ transport was supported by all four nucleotides. This is the first time that a diphosphonucleotide has been shown to support Ca²⁺ transport. A new nonhydrolysable triphospho TNPnucleotide, TNP-AMP-PCP was synthesized and shown to interact with the Ca²⁺ATPase in a similar way, in terms of superfluorescence, as the other TNP-nucleotides. It did not show the complex kinetics on inhibition of the Pcinduced superfluorescence by Ca²⁺, but neither did it accelerate the kinetics. It was concluded that TNP-nucleotides do not accelerate the E₂ ↔ E₁ transition under these conditions, possibly because of the presence of glycerol in the medium. In the second part of the study, it was shown that addition of small amounts of chelators EGTA, EDTA, BAPTA, DTPA, HEDTA and NTA to a Ca²⁺ transport assay in which the free Ca²⁺ concentration is monitored by Fluo-3 causes the Ca²⁺ATPase to pump to apparently lower levels as seen in the [Ca²⁺] lim fluorescence. Addition of chelator retards pump function in the sense that it takes longer for 50 nmols Ca²⁺ to be accumulated. Increased thermodynamic efficiency of the pump and contaminating heavy metal ions were considered as possible mechanisms. To some extend Zn²⁺ and Cd²⁺, but not Fe²⁺ and Cu²⁺, appeared to reverse the partial inhibition. While interpretation of the results is difficult, it is suggested that heavy metal ions interact with luminal loops of the Ca²⁺ATPase and enhance Ca²⁺ release under conditions of high luminal Ca²⁺ concentrations.